ANALYSIS OF COGNITIVE LOAD IN STUDENTS' BASIC MATHEMATICS COURSES REVIEWED FROM MATHEMATICAL ABILITIES - Nailul Authary; Muhammad Yani; M. Riski Alkhalisi (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2023)
Basic math courses contribute to strengthening basic math skills so students don't experience difficulties when they have to solve math-related problems in other courses. The reality in the field is that students still experience difficulties in learning basic mathematics caused by cognitive processes. The purpose of this study was to determine the cognitive load in basic mathematics courses in terms of students' mathematical abilities. This type of research is descriptive using a qualitative approach. There were 3 research subjects who were grouped based on mathematical abilities. The result of this research is that for subjects with high mathematical ability (S1), the cognitive load that appears the most is intrinsic cognitive load. The subject of moderate mathematical ability (S2) cognitive loads that appear most frequently are intrinsic and extraneous. Meanwhile, subjects with low mathematical abilities, (S3) experienced intrinsic, foreign and close burdensKeywords: cognitive load; students' basic mathematics; mathematical abilities